Rural sociology and community mobilization for sustainable growth - Yasser, Qaiser Rafique, 1983- (Hershey, PA : Information Science Reference, 2018)
'This book explores how global trends, state policies, and grassroots movements affect contemporary rural areas in both developed and developing countries. It also contains information on the contribution of the rural environment and its people to global agriculture, food security and the perpetuation of the human race'--
Private sector development in waste management in rural areas / Veronika Alhanaqtah, Tafila Technical University, Jordan, Omar Alhanaqtah, Tafila Technical University, Jordan, Antonina Pakhomova, South-Russian State Polytechnic University in the name of M. I. Platov, Russian Federation -- A module on the role of global economy policies and issues with focus on rural sociology and community mobilization for sustainable growth: experiential learning techniques (ELT) / Marites Maria Theresa Galing-Argonza, Isabela State University; Canadian University Dubai, Emirates Aviation University, United Arab Emirates -- Water resources management for sustainable development : international environmental law perspectives / Md. Mahfuzar Chowdhury, BRAC, Bangladesh -- Sustainable rural development / Shereen Khan, Sardar Bahadur Khan Women's University, Quetta, Pakistan -- Impact of water availability on rural development in Nigeria / Sinmi Abosede, Dr., Nigeria -- Rural aging, demise of the traditional family and the rise of new family structures in rural Turkey : evidences from the province of Kayseri / Ozan Hovardaoglu, Erciyes University, Turkey, Seda Calisir-Hovardaoglu, Erciyes University, Turkey -- Information access for rural women in Nigeria / Juliana Iwu-James, Covenant University, Nigeria, Nigeria, Jerome Idiegbeyan-ose, Covenant University, Nigeria, Goodluck Ifijeh, Covenant University, Nigeria, Chidi Segun-Adeniran, Covenant University, Nigeria -- Ugunwa esse, covenant university, nigeria -- Experiences and challenges of the Chinese rural education development : in the context of the rapid urbanization / Chenbing Wu, East China Normal University, China, Cong Lyu, East China Normal University, China, Jiacheng Li, East China Normal University, China.
Keywords: Sociology, Rural; Rural development; Sustainable development; Community development